2020
DOI: 10.1111/apt.15654
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women with inflammatory bowel disease: a 10‐year nationwide population‐based cohort study

Abstract: Background: Data relating to the association between inflammatory bowel disease (IBD) and pregnancy outcomes are lacking in Korea. Aims:To determine the incidence rates of pregnancy outcomes in women with IBD.Methods: A nationwide population study was performed using the Korean National Health Insurance claims database. A total of 2058 women with IBD consisting of ulcerative colitis (UC, n = 1469) and Crohn's disease (CD, n = 589) were pregnant between 2007 and 2016. We compared their incidence of pregnancy ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 42 publications
5
55
1
1
Order By: Relevance
“… 11 , 12 However, AMH levels are significantly lower during active disease and inversely correlate with the Crohn’s Disease Activity Index, 13 supporting the observation that fertility rates are reduced in active disease. 9 , 14 A nationwide Korean study found a 21% reduced live birth rate in women with moderate-to-severe IBD activity, while birth rates in women with quiescent or mildly active IBD were comparable with women without IBD. 14 IPAA surgery may also impair fertility, with infertility rates rising from 15 to 20% pre-IPAA to 48–63% post-IPAA.…”
Section: Fertilitymentioning
confidence: 99%
See 3 more Smart Citations
“… 11 , 12 However, AMH levels are significantly lower during active disease and inversely correlate with the Crohn’s Disease Activity Index, 13 supporting the observation that fertility rates are reduced in active disease. 9 , 14 A nationwide Korean study found a 21% reduced live birth rate in women with moderate-to-severe IBD activity, while birth rates in women with quiescent or mildly active IBD were comparable with women without IBD. 14 IPAA surgery may also impair fertility, with infertility rates rising from 15 to 20% pre-IPAA to 48–63% post-IPAA.…”
Section: Fertilitymentioning
confidence: 99%
“… 9 , 14 A nationwide Korean study found a 21% reduced live birth rate in women with moderate-to-severe IBD activity, while birth rates in women with quiescent or mildly active IBD were comparable with women without IBD. 14 IPAA surgery may also impair fertility, with infertility rates rising from 15 to 20% pre-IPAA to 48–63% post-IPAA. 15 , 16 This is attributed to reproductive organ damage from deep pelvic dissection, formation of scar tissue and adhesions, and the increased prevalence of dyspareunia post-operatively.…”
Section: Fertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Children with one parent with IBD have a 2-13 times higher risk of IBD. An especially active disease is associated with adverse birth outcomes, including spontaneous abortion, decreased live birth rate, low birth weight, and newborns too small for the gestational age [4]. Other concerns do not correlate with any unequivocal scientific findings: miscarriage, death, and congenital abnormalities are not significantly increased in patients with IBD and their children in general [4][5][6].…”
Section: Introductionmentioning
confidence: 99%